Anskueliggørelse af faglige relationer i brancheordbøger - Pedersen, Jette (LexicoNordica, 1994)
After a brief introduction to produet-line dictionaries, including the requirements for this particular type of LSP dictionary, intended dictionary functions and user categories are specified and the different ways in which these factors influence pre-lexicographical considerations discussed. On the basis of these introductory observations, an approach to the incorporation and structuring of information concerning the primary subject field covered by the dictionary is presented, taking into account systematic representation in an alphabetically structured dictionary. The components considered include an encyclopedic section in the outside matter as well as illustrations and definitions.